Decelerations, Tachycardia, and Decreased Variability: Have We Overlooked the Significance of Longitudinal Fetal Heart Rate Changes for Detecting Intrapartum Fetal Hypoxia?. Issue 3 (September 2017) - Vintzileos, A.M.; Smulian, J.C.
Abstract : ( Am J Obstet Gynecol . 2016;215(3):261–264) Fetal asphyxia usually occurs in low-risk pregnancies. This editorial supports the use of longitudinal assessment of fetal heart rate (FHR) changes during labor to emphasize the point that in many cases such as the evolution of category II (indeterminate) FHR patterns, evaluation of fetal status over time should include not only the last 15 to 30 minutes of the FHR tracing, but the entire labor. The high interobserver and intraobserver variabilities in the interpretation and management of the various FHR patterns are major shortcomings of electronic fetal monitoring (EFM).